Borden chantry - L'Amour, Louis (Ulverscroft, 1977)
The marshal's name was Borden Chantry. Young, lean, rugged, he's buried a few men in this two-bit cow town -- every single one killed in a fair fight. Then, one dark, grim day a mysterious gunman shot a man in cold blood. Five grisly murders later, Chantey was faced with the roughest assignment of his life--find that savage, trigger-happy hard case before he blasts apart every man in town... one by bloody one.
59365
Keywords: Large Print; Marshal; Gunman; Gun fight